(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2019)
The discourse of economy has gone by a constant tension between belonging to a Social Science (CS) and present prototypical features of a Basic Science (CB). However, evidence this hybridity poses a challenge for researchers of language, especially if these texts are part of the training of an economist. In particular, the Monetary Policy Report (IPOM) has not been studied from the linguistic point of view. In this context, this research search to answer the question whether the gender IPOM evidences such discursive tension of the discipline. To achieve this objective, it has opted for a methodology based on 2 dimensions: Production Context and Rhetorical-Functional Organization. After the analysis, the findings Integrally shows that the IPOM genre effectively demonstrates this tension with features more characteristic of the BS such as the use of mathematical resources and, on the other hand, SC traits, mainly associated to the modalization of the discourse in its central macromove.